A Comparison of Rapid Bacterial Methods to U.S. EPA‐Approved Methods for Biosolids. (1st July 2013) - Carner, Niccole; Carroll, Zachary S.; Long, Sharon C.
ABSTRACT: : The U.S. Environmental Protection Agency (U.S. EPA) specifies methods for testing microorganisms in biosolids, including U.S. EPA Methods 1680 and 1682 for fecal coliforms and Salmonella sp., respectively. However, these methods require 3 to 5 days to complete. For research or nonregulatory process monitoring purposes, it would be desirable to have a more rapid, less labor‐intensive method of enumerating these organisms. The purpose of this study was to compare a modified Colilert with Quanti‐Tray/2000 method to U.S. EPA Method 1680 for enumeration of fecal coliforms and E. coli, and to compare spread plating on xylose‐lysine deoxycholate (XLD) supplemented with 10 μg/L novobiocin to U.S. EPA Method 1682 for Salmonella sp. in biosolids. These alternative enumeration methods require only 1 day to complete, using fewer costly materials. This limited study indicated that the more rapid methods provide results that are statistically comparable to U.S. EPA methods under most conditions and would be acceptable for rapid, nonregulatory data collection.